Analysis of Translation Techniques in Chinese Drama Series Titles: A Study Based on Molina and Albir's 18 Techniques - Leni Cahyati; Andi Filsah Muslimat; Khafifa Fuji Lestari (Universitas Negeri Semarang, 2026)
This study aims to identify and categorize the translation techniques utilized in converting Chinese drama series titles into English. Utilizing Molina and Albir’s (2002) theoretical framework, which encompasses 18 translation techniques, this research examines 100 Chinese drama series titles available on the iQIYI and WeTV platforms along with their English translations. A descriptive-qualitative method with a content analysis approach was employed. The findings indicate that 12 out of the 18 techniques were identified, with Literal Translation, Modulation, and Discursive Creation emerging as the most frequently employed technique, accounting for 16,67% of the cases, followed by borrowing, adaptation, equivalence, and Amplification. These results demonstrate that translators tend to prioritize semantic accessibility for international audiences while striving to maintain Chinese cultural identity within the translated titles.